EVALUATION OF SPHERIPOL POLYMERIZATION PROCESS FOR PRODUCING POLYPROPYLENE - Fajar Riyanto, Ari
Propylene gas is the main raw material for polypropylene production. The construction of the Residual Fluid Catalytic Cracking (RFCC) unit at PT XYZ has resulted in increased production of propylene gas. PT XYZ plans to build a polypropylene production plant with a capacity of 250 thousand tons per year. The Spheripol technology process is a type of polymerization process released by Lyondellbasell lisensors and currently almost one third of global polypropylene production uses this technology. In this technology consists of 4 reactors, 1 unit reactor prepolymerization, 2 units reactor loops (liquid pool) installed in series for the production of homopolymer or random copolymers and 1 unit bed fluidization reactor for the production of high impact polypropylene (hiPP). This research is focused on making a simulation model of the Spheripol process in accordance with the needs of the production capacity and the quality of PT. XYZ, they are the production capacity of polypropylene of 32400 kg / hour and melt flow rate (MFR) of 10. The performance of the process model that has been made is evaluated by varying the operating conditions that affect the quality of the polypropylene product produced. Evaluation results show that increasing the concentration of hydrogen into the reactor R-102 will affect the performance of the polymerization unit, specifically the MFR value of the product produced, and the magnitude of the conversion of propylene to polypropylene. In addition, the high temperature in the reactor R-102 can cause the conversion to be high too, causing the slurry density to increase towards the pump so that the resulting MFR of the product also becomes high. To produce MFR of 9,91797 in the resulting polypropylene the required H2 content entering the R-102 and R-103 reactors is 94,966 ppm and the temperature in the Reactor R-102 is about 65 C and the temperature in the Reactor R-103 is about 70 C.